DECENTRALIZATION AND THE PEOPLE-CENTERED HUMAN RESOURCE MANAGEMENT MODEL TERRITORIAL COMMUNITIES - Dmytro Dzvinchuk; Viktor Petrenko; Ivan Lopushynskyi (Публічне управління та регіональний розвиток)
The article, based on the analysis of the experience of countries that have already undergone transformational changes on the way to decentralization of management, proposes an original hierarchical model of people-centered management of human resources of territorial communities; it is shown that in the processes of transformation of many countries of the world, their governments developed and implemented programs that provided for various forms of decentralization, as society grew interested in its own role as a partner of governments and in finding new ways of interaction; it was found out that the leading role in the processes of change and further successful and sustainable development of territorial communities in countries with an evolutionarily formed market economy belongs to human resources, and the effective use of this most important resource component is determined by the level of ownership and the ability of personnel of management systems to use modern technologies of human resources management; it was found that in modern Ukrainian society there is a growing trend of citizens' aspirations and desires to actively influence the level of their well-being and well-being through participation in decision-making, which corresponds to promising European experience; based on the results of the analysis of the world experience of implementing decentralization plans and establishing the expediency of involving in the management of newly created communities not only leaders and officials of local self-government bodies, but also all interested representatives of human resources, it has been proven that, that a critical problem of the process is the proper mastery and proper use in management processes by the leaders and staff of local self-government bodies of newly formed territorial communities of the theoretical and practical foundations of human-centered human resource management technologies.